Exploiting coastal altimetry to improve the surface circulation scheme over the central Mediterranean Sea. Issue 7 (16th July 2016) - Jebri, Fatma; Birol, Florence; Zakardjian, Bruno; Bouffard, Jérome; Sammari, Cherif
Abstract: This work is the first study exploiting along track altimetry data to observe and monitor coastal ocean features over the transition area between the western and eastern Mediterranean Basins. The relative performances of both the AVISO and the X‐TRACK research regional altimetric data sets are compared using in situ observations. Both products are cross validated with tide gauge records. The altimeter‐derived geostrophic velocities are also compared with observations from a moored Acoustic Doppler Current Profiler. Results indicate the good potential of satellite altimetry to retrieve dynamic features over the area. However, X‐TRACK shows a more homogenous data coverage than AVISO, with longer time series in the 50 km coastal band. The seasonal evolution of the surface circulation is therefore analyzed by conjointly using X‐TRACK data and remotely sensed sea surface temperature observations. This combined data set clearly depicts different current regimes and bifurcations, which allows us to propose a new seasonal circulation scheme for the central Mediterranean. The analysis shows variations of the path and temporal behavior of the main circulation features: the Atlantic Tunisian Current, the Atlantic Ionian Stream, the Atlantic Libyan Current, and the Sidra Gyre. The resulting bifurcating veins of these currents are also discussed, and a new current branch is observed for the first time. Key Points: Assessment of conventional altimetry over the wide shelf of Tunisia Monitoring seasonal variability of the Atlantic Tunisian Current/Atlantic Ionian Stream and associated features from altimetry Coastal altimetry is able to detect the slope circulation in the central Mediterranean Sea